Parmenides as a precursor of Plato’s dialectics - Fernández Mouján, Raimundo (Revista Archai, 2019)
Taking as a standpoint a certain interpretation of Plato’s dialectics, and a reading of Monique Dixsaut’s article “Platon et le lógos de Parménide”, we investigate in this work the possibility of identifying in Parmenides’ Poem some of the elements that later will be fundamental in the constitution of dialectics in Plato’s dialogues. The rejection of the name as the means and depositary of knowledge, the necessary mediation of the lógos, and the insistence in the importance of knowing also the nature of error and deceit, are some of these elements that we encounter already in Parmenides, and that will be fundamental for the gradual development of the method proposed by Plato.